How to Prevent K-Wire Bounce in Oblique Supracondylar Humerus Fractures. Issue 12 (December 2018) - Iobst, Christopher; Thompson, R. Gil; Grauer, Jordan; Wheeler, Peter
Abstract : Summary: Supracondylar humerus fractures with an obliquely oriented fracture pattern can pose a clinical challenge in obtaining adequate fixation. Traditionally, 1.6-mm Kirchner wires are used for fracture fixation when pinning pediatric supracondylar humerus fractures. However, when pinning across obliquely oriented fractures, the angle of pin inclination may increase to the point where the 1.6-mm k-wire cannot penetrate the far cortex. We have found that, when pinning oblique supracondylar humerus fractures, utilization of a 2.0-mm k-wire can assist the surgeon in obtaining bicortical purchase. We present a cadaveric study demonstrating the maximal angles at which both 1.6-mm and 2.0-mm k-wires will penetrate the far cortex. This technical trick can give surgeons a relatively simple solution to treat these difficult fractures.